Hydrogeochemistry and water management in a Venezuelan heavy oil reservoir: Evidence from the Carabobo field - Beatriz Angulo; Tiziano Boschetti; Felipe Quintero (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Re-evaluating probable maximum precipitation estimates: sensitivity to transposition domains and storm rotation using modern datasets - Gabriel Perez; Scott T. DeNeale; Shih-Chieh Kao; Felipe Quintero (Journal of Hydrology, 2026)

Contract design under conflict and tenure informality: Evidence from PES preferences in the Colombian Amazon - Hernán Felipe Trujillo Quintero; Jessica Leahy; Adam Daigneault (Forest Policy and Economics, 2026)

Innovative plant-based drinks produced by pulse spray drying: An approach on physicochemical properties and microbial assessment - Adriana Dantas; Marc Piella-Rifà; Pere Gou; Anna Jofré; Gisela Quinteros; Xavier Felipe (Innovative Food Science & Emerging Technologies, 2026)

Wheat bran solid-state fermentation for enzymatic extract production and dye decolorization with physicochemical characterization of residual biomass - Andrés Vargas-Lopera; Felipe Mejia-Otalvaro; Carolina Velásquez-Quintero; Andrés Merino-Restrepo; Angelina Hormaza-Anaguano (Biocatalysis and Agricultural Biotechnology, 2026)

Trait-explicit approaches cast new light on fragmentation’s effects on biodiversity - Andres Felipe Suárez-Castro; Zachary Hajian-Forooshani; Martha Paola Barajas Barbosa; Gabriella Damasceno; Matthias Grenié; Natalia Ocampo-Peñuela; Rachel R.Y. Oh; Juan Carvajal-Quintero; Beatriz Prado-Monteiro; Jonathan M. Chase (Trends in Ecology & Evolution, 2026)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Cork oak woodlands and decline: a social-ecological review and future transdisciplinary approaches - Margarida Lopes-Fernandes; Ernesto Martínez-Fernández; Rui Alves; Daniel Boa-Nova; Cristina Branquinho; Miguel N Bugalho; Felipe Campos-Mardones; Agustin Coca-Pérez; Amélia Frazão-Moreira; Marco Marques; Javier Moreno-Ortiz; Octávio Paulo; et al. (Agroforestry Systems, 2024)
Cork oak woodlands are socio-ecosystems recognized as biodiversity hotspots, a fundamental economic source for companies and local communities as well as an identitarian landscape for residents and visitors. Cork oak woodlands, however, are facing tree mortality and lack of regeneration. Considering the oak decline scenario, we present Iberian cork oak montado/dehesa as a socio-ecosystem facing climate change, management transformations, local knowledge crisis and social uncertainty. We review montado s/ dehesa s research through time and by different scholar perspectives. We defend that from an interdisciplinary and transdisciplinary perspective, including the experience and evidence observed in terrain, debate should be stimulated, and novel conceptual approaches may contribute to finding solutions. We argue that the confluence of ecology, genetics, anthropology and local knowledge can be explored to unveil the complexities and the challenges of these socio-ecosystems and contribute to prevent and mitigate threats to it. We propose a methodological approach built together with scientists, managers and workers, that can explore oak translocations, socio-ecological interactions models, knowledge transfer and other ways to overcome Iberian cork oak woodlands socio-environmental crisis.

Effect of the incorporation of sugars and citric acid in low cocoa butter emulsions - Andrés Felipe Caballero-Tovar; Angélica Piedad Sandoval-Aldana; Alejandro Fernández-Quintero (Journal of Food Engineering, 2024)

Projected changes in annual maximum discharge for Iowa communities - Alexander Michalek; Felipe Quintero; Gabriele Villarini; Witold F. Krajewski (Journal of Hydrology, 2023)

Applicability of a flood forecasting system for Nebraska watersheds - Sinan Rasiya Koya; Nicolas Velasquez Giron; Marcela Rojas; Ricardo Mantilla; Kirk Harvey; Daniel Ceynar; Felipe Quintero; Witold F. Krajewski; Tirthankar Roy (Environmental Modelling & Software, 2023)

Microearthquakes in the Guadalajara Metropolitan Zone, Mexico: evidence from buried active faults in Tesistán Valley, Zapopan - Claudia Quinteros-Cartaya; Guillermo Solorio-Magaña; Francisco Javier Núñez-Cornú; Felipe de Jesús Escalona-Alcázar; Diana Núñez (Natural Hazards, 2023)
Numerous microearthquakes, M L ≤ 3.8, corresponding to background seismicity and swarms were observed from September 3, 2017, to January 1, 2018, mainly in the Tesistán Valley, north of the Guadalajara Metropolitan Zone (GMZ). We located 188 tectonic microearthquakes and identified 11 clusters of similar events from a spatio-temporal analysis and waveform cross-correlations. Our results confirm the presence of continuous seismicity in the GMZ that long went unobserved. Most M L ≥ 2.5 events and some clustered events are located in the northeastern Tesistán, close to the NNE-SSW fault corresponding to the eastern edge of the Zapopan Graben, a structure evidenced by 2015–2016 seismicity. Seismicity recorded during 2020 by a recent local seismic network installed in Zapopan reaffirms that frequent microseismicity is related to active faults that cross the cities of Zapopan and Guadalajara. The microseismicity distribution suggests minor faults with the same orientation and sense of displacement as the main structures bounding the Zapopan Graben, which corresponds to structures known as synthetic faults. This arrangement is common within the Basin and Range tectonic province. The seismicity in the northeast boundary of Jalisco Block is closely related to faults formed by Cenozoic deformation events that might be reactivated due to modern crustal dynamics. Active faults and the possibility of synthetic structures are a hypothesis that necessitates long-term seismic monitoring in order to assess the seismic hazard in the GMZ, which is a crucial factor for urban planning.

Spatio-temporal distribution of particulate matter and wood-smoke tracers in Temuco, Chile: A city heavily impacted by residential wood-burning - Maria Elisa Quinteros; Estela Blanco; Janeet Sanabria; Felipe Rosas-Diaz; Carola A. Blazquez; Salvador Ayala; Juan Pablo Cárdenas-R; Elizabeth A. Stone; Keely Sybesma; Juana Maria Delgado-Saborit; Roy M. Harrison; Pablo Ruiz-Rudolph (Atmospheric Environment, 2023)

Rainfed agriculture and firewood extraction have contrasting changes on biocrust functional groups and soil N dynamics in a tropical dryland - Jessica Sosa-Quintero; Felipe García-Oliva; Héctor Godínez-Alvarez (Journal of Arid Environments, 2023)

Comparative analysis of performance and mechanisms of flood inundation map generation using Height Above Nearest Drainage - Zhouyayan Li; Felipe Quintero Duque; Trevor Grout; Bradford Bates; Ibrahim Demir (Environmental Modelling & Software, 2023)

On the role of atmospheric simulations horizontal grid spacing for flood modeling - Felipe Quintero; Gabriele Villarini; Andreas F. Prein; Witold F. Krajewski; Wei Zhang (Climate Dynamics, 2022)

Identification and genotyping of porcine circovirus type II (PCV2) in Mexico - Felipe Bedolla López; María E. Trujillo Ortega; Susana Mendoza Elvira; Victor Quintero Ramírez; Rogelio Alonso Morales; Humberto Ramírez-Mendoza; Jose I. Sanchez-Betancourt (VirusDisease, 2018)